Effect of potassium and plant geometry on the growth and yield of cumin (Cuminum cyminum L.) in Helmand Afghanistan - Shir Agha Baheer; Anchal Dass; Qudratullah Ehsan; Aye Aye San; Teekam Singh; Arjun Singh (Annals of Agricultural Research, 2026)
A field experiment was carried out at the research farm of Helmand University, Afghanistan during December 2021 to April 2022 to investigate the effect of different potassium levels (0, 40, 80,120,160 and 200 kg K2SO4 ha-1) and plant geometries (20 cm×10 cm and 30 cm ×10cm) on the growth and yield of cumin (Cuminum cyminum L.). The experiment was laid-out in a randomized complete block design (RCBD) replicated three times. The results revealed that wider spacing (30 cm×10 cm) exhibited greater plant height (33.56 cm), seed yield 472.6 kg ha-1, 1000-seed weight (3.55 g), dry matter accumulation (3.79 g plant-1), umbels plant-1 (26.1), seeds umbel-1 (23.7), umbellate umbel-1 (5.11), straw yield (767.16 kg ha-1), biological yield (1252.9 kg/ha), harvest index (37.5 %), and B: C ratio (2.73), production efficiency (4.29 kg ha-1 day-1), water-use efficiency (1.02 kg ha-1 mm-1) and monetary efficiency (756.3 AFN ha-1 day -1). Application of potassium at the highest rate (200 kg K2SO4 ha-1) recorded the highest growth, yield attributes, yield, economics and resource-use efficiencies (production efficiency, water-use efficiency and monetary efficiency). Likewise, plots that were treated with wider spacing and the highest rate of potassium (200 kg K2SO4 ha-1) produced higher yield, and yield components (200 >160 >120 >80 >40 > control). However, the difference between 160 and 200 kg K2SO4 ha-1 was not significant. Overall, results of this study showed that cumin growth, yield and yield components increased with wider spacing (30 cm × 10 cm) and with the application of 160-200 kg K2SO4 ha-1 potassium level; seed yield and important yield attributes did not increase significantly beyond 160 K2SO4 ha-1. Thus, the study suggests that cumin should be planted at (30 cm × 10 cm) and fertilized with 160 K2SO4 ha-1.